A Brief Discussion on Curdling Technology, Microbiological Risks and Contaminants of Fermented Milk Named Biisim Missiga - Hama, Cissé; Oumarou, Zongo; Bakary, Tarnagda; Ousman, Abdoullahi Hissein; Boureima, Kagambèga; Ganamé, Ouédraogo Abasse; Adama, Sawadogo; Yves, Traoré; Aly, Savadogo (Journal of Food Technology Research, 2019)
The objective of this study was to evaluate endogenous curdling knowledge, microbiological hazards and other contaminants of Bîisim missiga. Thus, a survey was conducted among local producers to collect information on curdling technologies in five cities to Burkina Faso. The quality of Bîisim missiga samples collected was assessed according to standard microbiological criteria. Contaminants and their sources have been identified according to literature review. The results of this survey revealed that fresh and powdered milk are the most used raw materials to production of Bîisim missiga. Curdling technologies are similar in cities surveyed. Microbiological quality of Bîisim missiga analysed was unsatisfactory according to criteria used. The presence of pathogenic potential was detected during microbiological analyses. Three types of contaminations have been identified according to literature. In sum, this study revealed that the Bîisim missiga analysed do not comply with the criteria in force. Corrective measures must be taken to improve the quality of Bîisim missiga sold in Burkina Faso.